2021
DOI: 10.21037/atm-21-3777
|View full text |Cite
|
Sign up to set email alerts
|

Combined transcriptomic and lipidomic analysis of D-4F ameliorating bleomycin-induced pulmonary fibrosis

Abstract: Background: Idiopathic pulmonary fibrosis (IPF) is a progressive lung disease that leads to respiratory failure, and for which there is no effective treatment. Apolipoprotein A-1 (ApoA-1) has been reported to ameliorate the bleomycin (BLM)-induced IPF model. Methods:To examine the function of D-4F, an ApoA-1 mimetic polypeptide, in IPF, we used an in-vivo BLM-induced model. We assigned mice into the following 3 groups: the Blank Group (BLK Group), the Bleomycin Treatment Group (Model Group), and the D-4F Inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 54 publications
1
0
0
Order By: Relevance
“…The alveoli, the most active lipid metabolizer in the lung, requires surfactant lipids for the synthesis of respiration ( Agudelo et al, 2020 ), and PC and PE are the key lipids of pulmonary surfactants, and the total saturation of silicosis rat lungs increases ( Srivastava and Misra, 1986 ). Xia et al (2021) also confirmed that the contents of PC and PE in bleomycin-induced pulmonary fibrosis rats were increased. This is consistent with the results of this study.…”
Section: Discussionsupporting
confidence: 65%
“…The alveoli, the most active lipid metabolizer in the lung, requires surfactant lipids for the synthesis of respiration ( Agudelo et al, 2020 ), and PC and PE are the key lipids of pulmonary surfactants, and the total saturation of silicosis rat lungs increases ( Srivastava and Misra, 1986 ). Xia et al (2021) also confirmed that the contents of PC and PE in bleomycin-induced pulmonary fibrosis rats were increased. This is consistent with the results of this study.…”
Section: Discussionsupporting
confidence: 65%